Optimization of Business Processes in E-Commerceusing Artificial Intelligence Methods and Algorithms - E. S. Piskun; D. V. Nuansengsy; E. N. Kotsko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
The paper discusses methods and algorithms of artificial intelligence aimed at automating and optimizing business processes in e-commerce. The possibilities of using artificial intelligence to personalize customer offers, predict consumer behavior and segment customers using machine learning methods are presented. The features of the application of artificial intelligence in such large companies as Amazon, Walmart, OZON and Netflix are analyzed, where it allows improving the accuracy of forecasts and automating decision-making processes. It is proposed to use natural language processing methods and neural networks to automatically generate advertising descriptions of goods, which helps to increase the effectiveness of marketing strategies and reduce costs.